ANALYSIS OF PROBLEM AREAS OF DENTAL CARE IN THE ALTAI TERRITORY ACCORDING TO THE SURVEY OF DOCTORS - Светлана Ивановна Токмакова; Людмила Юрьевна Побединская; Ольга Владимировна Бондаренко; Юлия Васильевна Луницына; Мария Ивановна Фролова; Людмила Николаевна Тупикова; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес; Яэль Центер (Медицина в Кузбассе)
The identification of problems in the provision of dental care to the population of the Altai Territory in medical and preventive institutions of the public and private sector is relevant.